Highly asymmetric large-deformation lead-free ferroelectric ceramic material and preparation method thereof

By adopting specific stoichiometric lead-free ferroelectric ceramic materials and asymmetric electrode design, the problem of insufficient strain performance of existing lead-free ferroelectric ceramic materials is solved, and high deformation driving performance and low cost preparation are achieved, which is suitable for industrial production.

CN119504257AInactive Publication Date: 2025-02-25GUILIN UNIV OF ELECTRONIC TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411637190.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The maximum strain S of existing lead-free ferroelectric ceramic materials generally does not exceed 0.7, making it difficult to improve its driving strain performance. The preparation process of the dual-wafer design is complex, costly, and difficult to control carefully.

Method used

Lead-free ferroelectric ceramic materials are prepared by stoichiometric 0.733(Bi1/2Na1/2)TiO3-0.267(Ca1/3Bi2/9Sr1/3)Cu3(Ti1/2Zr1/2)4O12, and synthesized by ball milling, drying, and insulation. The steps of cold isostatic molding, sintering and screen printing of asymmetric electrodes are produced to produce lead-free ferroelectric ceramic materials with highly asymmetric large deformation.

Benefits of technology

The high deformation driving performance of lead-free ferroelectric ceramic materials is achieved, with the maximum electrostatic deformation S=3.6%, which is far exceeding the strain performance of traditional ferroelectric ceramics. The preparation method is simple and low-cost, and it is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504257A_ABST
    Figure CN119504257A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lead-free ferroelectric ceramic materials, in particular to a lead-free ferroelectric ceramic material with high asymmetric large deformation and a preparation method thereof.The preparation method of the lead-free ferroelectric ceramic material with the high asymmetric large deformation comprises the steps that pure raw materials are weighed and analyzed according to the stoichiometric ratio of 0.733 (Bi1 / 2Na1 / 2) TiO3-0. 267 (Ca1 / 3Bi2 / 9Sr1 / 3) Cu3 (Ti1 / 2Zr1 / 2) 4O12, all the raw materials are mixed and subjected to ball milling, and powder is obtained; drying the raw materials after ball milling, and performing heat-preservation synthesis on the dried raw materials to prepare powder; mixing and ball-milling the synthesized powder, drying, carrying out cold isostatic pressing molding under 80Mpa, carrying out heat preservation, sintering into compact ceramic, and cooling to room temperature; screen-printing a silver electrode on one side of the sintered compact ceramic, screen-printing a gold electrode on the other side of the sintered compact ceramic, and performing heat preservation to form an asymmetric-size electrode; the method can be used for preparing the lead-free ferroelectric ceramic material with high deformation driving performance, and has the advantages of simple preparation method and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lead-free ferroelectric ceramic materials, and in particular to a lead-free ferroelectric ceramic material with highly asymmetric large deformation and a preparation method thereof. Background Art

[0002] Ferroelectric ceramic materials refer to a class of materials with ferroelectric effect. They are intelligent materials. Their electromechanical conversion and spontaneous polarization make ferroelectric ceramics widely used in sensing, energy conversion, energy storage, refrigeration, catalysis, photovoltaics, flexible devices and other fields. They play a vital role in national defense and people's livelihood, and are one of the indispensable high-tech new materials. Traditional ferroelectric ceramics are mainly based on lead-containing lead zirconate titanate (PZT) materials, the main component of which is lead oxide (more than 60-70%). During the production, use and post-disposal processing, they will cause damage to humans and the ecological environment. With the increasing awareness of environmental protection, finding high-performance lead-free ferroelectric ceramics that can replace traditional lead-based ceramic materials has become an urgent market demand.

[0003] Among the lead-free ferroelectric ceramics currently under development, bismuth sodium titanate (Bi1 / 2Na1 / 2)TiO3 (BNT for short) has shown great application potential due to its high electrostrain performance. However, the maximum strain S of the lead-free ceramics of this system generally does not exceed 0.7, and it is difficult to further increase it. In order to increase its driving strain performance, the current strategy is to design it into a double-chip, by extending one chip and shortening the other chip, and jointly generating bending deformation to increase its driving performance. However, the preparation process of this double-chip design is more complicated than that of ceramics, with high cost and difficult to precisely control. Therefore, a simple and low-cost preparation method is needed to prepare lead-free ferroelectric ceramic materials with high deformation driving performance. Summary of the invention

[0004] The purpose of the present invention is to provide a lead-free ferroelectric ceramic material with highly asymmetric large deformation and a preparation method thereof, which can prepare a lead-free ferroelectric ceramic material with high deformation driving performance and has the advantages of simple preparation method and low cost.

[0005] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a lead-free ferroelectric ceramic material with highly asymmetric large deformation, comprising:

[0006] According to 0.733 (Bi 1 / 2 Na 1 / 2 )TiO3-0.267(Ca 1 / 3 Bi 2 / 9 Sr 1 / 3 )Cu3(Ti 1 / 2 Zr 1 / 2 )4O 12The analytically pure raw materials Bi2O3, Na2CO3, CaCO3, SrCO3, ZrO2, CuO and TiO2 are weighed respectively according to the chemical measurement, all the raw materials are mixed and ball-milled, the raw materials are dried after ball-milling, and the raw materials are kept warm and synthesized after drying to obtain powder;

[0007] The synthesized powders are mixed and ball-milled, dried, cold isostatically pressed at 80 MPa, sintered into dense ceramics after heat preservation, and cooled to room temperature in air;

[0008] Silver electrodes are screen-printed on one side of the sintered dense ceramic and gold electrodes are screen-printed on the other side. The center positions of the two surface electrodes are the same. After heat preservation, they become asymmetric electrodes of size, thereby obtaining a lead-free ferroelectric ceramic material with highly asymmetric large deformation.

[0009] Wherein, the above-mentioned 1 / 2 Na 1 / 2 )TiO3-0.267(Ca 1 / 3 Bi 2 / 9 Sr 1 / 3 )Cu3(Ti 1 / 2 Zr 1 / 2 )4O 12 The analytically pure raw materials Bi2O3, Na2CO3, CaCO3, SrCO3, ZrO2, CuO and TiO2 are weighed respectively according to the chemical measurement, all the raw materials are mixed and ball-milled, and the raw materials are dried after ball-milling. After drying, the raw materials are kept warm for synthesis. In the step of obtaining the powder, the ball-milling time is 24 hours, the insulation temperature is 910°C, and the insulation time is 3 hours.

[0010] The synthesized powders are mixed and ball-milled and then dried, cold isostatically pressed at 80 MPa, sintered into dense ceramics after insulation, and cooled to room temperature in air. The ball-milling time is 24 hours, the insulation temperature is 1080°C, and the insulation time is 1 hour.

[0011] Among them, in the step of screen-printing a silver electrode on one side of the sintered dense ceramic and a gold electrode on the other side, with the center positions of the two surface electrodes being the same, and forming asymmetric electrodes of size after insulation to obtain a lead-free ferroelectric ceramic material with highly asymmetric large deformation, the insulation temperature is 600°C and the insulation time is 30 minutes.

[0012] Wherein, the radius ratio of the silver electrode to the gold electrode is 3:6.3.

[0013] In a second aspect, the present invention further provides a lead-free ferroelectric ceramic material with a high degree of asymmetric large deformation, which is prepared by the lead-free ferroelectric ceramic material preparation method with a high degree of asymmetric large deformation, and the composition of the lead-free ferroelectric ceramic material with a high degree of asymmetric large deformation is 0.733 (Bi1 / 2 Na 1 / 2 )TiO3-0.267(Ca 1 / 3 Bi 2 / 9 Sr 1 / 3 )Cu3(Ti 1 / 2 Zr 1 / 2 )4O 12 .

[0014] The present invention discloses a lead-free ferroelectric ceramic material with highly asymmetric large deformation and a preparation method thereof. The lead-free ferroelectric ceramic material prepared by the preparation method of the present invention has very excellent electro-induced large deformation performance. Different from the traditional ferroelectric ceramic strain, large asymmetric deformation is generated by the joint design of components and asymmetric electrodes of size. Its highly asymmetric maximum electro-induced deformation S=3.6%, far exceeding the strain of bulk ferroelectric ceramic materials in the prior art, realizes the deformation performance of complex dual-chip in simple ceramics, and has the advantages of being environmentally friendly and having stable performance. The preparation method of the present invention is simple, low-cost, and suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.

[0016] Figure 1 The present invention is a flow chart of a method for preparing a lead-free ferroelectric ceramic material with highly asymmetric large deformation.

[0017] Figure 2 Schematic diagram of the electrostatic loop (a) and strain curve (b) of BNT-based ceramics.

[0018] Figure 3 It is a schematic diagram of the disappearance of the critical component negative strain when the non-ergodic relaxation state transforms into the ergodic relaxation state.

[0019] Figure 4 It is a schematic diagram of the highly asymmetric high deformation output achieved by the critical components and asymmetric electrodes of the present invention. DETAILED DESCRIPTION

[0020] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0021] First, see Figure 1 ,in, Figure 1 The present invention is a flow chart of a method for preparing a lead-free ferroelectric ceramic material with highly asymmetric large deformation.

[0022] The present invention provides a method for preparing a lead-free ferroelectric ceramic material with highly asymmetric large deformation, comprising:

[0023] S1 is 0.733 (Bi 1 / 2 Na 1 / 2 )TiO3-0.267(Ca 1 / 3 Bi 2 / 9 Sr 1 / 3 )Cu3(Ti 1 / 2 Zr 1 / 2 )4O 12 The analytically pure raw materials Bi2O3, Na2CO3, CaCO3, SrCO3, ZrO2, CuO and TiO2 are weighed respectively according to the chemical measurement, all the raw materials are mixed and ball-milled, the raw materials are dried after ball-milling, and the raw materials are kept warm and synthesized after drying to obtain powder;

[0024] Wherein, the above-mentioned 1 / 2 Na 1 / 2 )TiO3-0.267(Ca 1 / 3 Bi 2 / 9 Sr 1 / 3 )Cu3(Ti 1 / 2 Zr 1 / 2 )4O 12 The analytically pure raw materials Bi2O3, Na2CO3, CaCO3, SrCO3, ZrO2, CuO and TiO2 are weighed respectively according to the chemical measurement, all the raw materials are mixed and ball-milled, and the raw materials are dried after ball-milling. After drying, the raw materials are kept warm for synthesis. In the step of obtaining the powder, the ball-milling time is 24 hours, the insulation temperature is 910°C, and the insulation time is 3 hours.

[0025] In the embodiment of the present invention, according to 0.733 (Bi 1 / 2 Na 1 / 2 )TiO3-0.267(Ca 1 / 3 Bi 2 / 9 Sr 1 / 3 )Cu3(Ti 1 / 2Zr 1 / 2 )4O 12 The analytically pure raw materials Bi2O3, Na2CO3, CaCO3, SrCO3, ZrO2, CuO and TiO2 were weighed respectively and put into a ball mill. Zirconia was used as grinding balls and anhydrous ethanol was used as ball milling medium. The mixture was fully mixed and ball milled for 24 hours. The grinding balls were separated and the raw materials were dried. The dried powder was pressed into a large green body, placed in a high-alumina crucible with a cover, and synthesized at 910°C for 3 hours.

[0026] The powders synthesized by S2 are mixed and ball-milled, then dried, cold isostatically pressed at 80 MPa, sintered into dense ceramics after heat preservation, and cooled to room temperature in air;

[0027] The synthesized powders are mixed and ball-milled and then dried, cold isostatically pressed at 80 MPa, sintered into dense ceramics after insulation, and cooled to room temperature in air. The ball-milling time is 24 hours, the insulation temperature is 1080°C, and the insulation time is 1 hour.

[0028] In the embodiment of the present invention, the synthesized powders are mixed and ball-milled for 24 hours and then dried, cold isostatically pressed at 80 MPa, and then sintered into dense ceramics by microwave at 1080° C. for 60 minutes, and then quickly cooled to room temperature in air.

[0029] S3 screen-prints a silver electrode on one side of the sintered dense ceramic and a gold electrode on the other side. The centers of the two surface electrodes are at the same position. After heat preservation, the electrodes are asymmetric in size, and a lead-free ferroelectric ceramic material with highly asymmetric large deformation is obtained.

[0030] Among them, in the step of screen-printing a silver electrode on one side of the sintered dense ceramic and a gold electrode on the other side, with the center positions of the two surface electrodes being the same, and forming asymmetric electrodes of size after insulation to obtain a lead-free ferroelectric ceramic material with highly asymmetric large deformation, the insulation temperature is 600°C and the insulation time is 30 minutes.

[0031] Wherein, the radius ratio of the silver electrode to the gold electrode is 3:6.3.

[0032] In an embodiment of the present invention, a dense ceramic sample after sintering has a silver electrode with a diameter of 3 mm screen-printed on one side and a gold electrode with a diameter of 6.3 mm screen-printed on the other side. The centers of the two surface electrodes are at the same position. The sample is kept at 600°C for 30 minutes to form an asymmetric electrode, thereby obtaining a lead-free ferroelectric ceramic material with highly asymmetric large deformation.

[0033] In order to better understand the present invention, a specific preparation process is used for illustration below.

[0034] First, according to 0.733 (Bi 1 / 2 Na 1 / 2 )TiO3-0.267(Ca 1 / 3 Bi 2 / 9 Sr 1 / 3 )Cu3(Ti 1 / 2 Zr 1 / 2 )4O 12 The analytically pure raw materials Bi2O3, Na2CO3, CaCO3, SrCO3, ZrO2, CuO and TiO2 were weighed respectively and put into a ball mill. Zirconia was used as grinding balls and anhydrous ethanol was used as ball milling medium. The mixture was fully mixed and ball milled for 24 hours. The grinding balls were separated and the raw materials were dried. The dried powder was pressed into a large green body, placed in a high-alumina crucible with a cover, and synthesized at 910°C for 3 hours.

[0035] Next, the synthesized powders were mixed and ball-milled for a second time for 24 hours and then dried, cold isostatically pressed at 80 MPa, sintered into dense ceramics by microwave at 1080°C for 60 minutes, and then rapidly cooled to room temperature in air.

[0036] Then, after sintering, a silver electrode with a diameter of 3 mm was screen-printed on one side of the dense ceramic sample, and a gold electrode with a diameter of 6.3 mm was screen-printed on the other side. The center positions of the two surface electrodes were the same, and the sample was kept at 600°C for 30 minutes to form an asymmetric electrode.

[0037] Finally, the deformation output properties of the prepared ceramics were measured using a ferroelectric tester.

[0038] The obtained product has been experimentally measured to have very excellent asymmetric deformation drive output performance, with a maximum deformation S=3.6%. The preparation process is simple, the cost is low, and it is suitable for large-scale industrial production.

[0039] The present invention discloses a method for preparing a lead-free ferroelectric ceramic material with highly asymmetric large deformation. The lead-free ferroelectric ceramic material prepared by the preparation method of the present invention has very excellent electro-induced large deformation performance. Different from the traditional ferroelectric ceramic strain, large asymmetric deformation is generated by the joint design of components and asymmetric electrodes of size. The highly asymmetric maximum electro-induced deformation S=3.6%, which far exceeds the strain of bulk ferroelectric ceramic materials in the prior art. The deformation performance of complex dual-chips is realized in simple ceramics, and the material has the advantages of being environmentally friendly and having stable performance. The preparation method of the present invention is simple, low-cost, and suitable for large-scale industrial production.

[0040] Second, see Figure 2-Figure 4 , Figure 2 Schematic diagram of the electrostatic loop (a) and strain curve (b) of BNT-based ceramics. Figure 3 This is a schematic diagram of the disappearance of the critical component negative strain when the non-ergodic relaxation state transforms into the ergodic relaxation state. Figure 4 It is a schematic diagram of the highly asymmetric high deformation output achieved by the critical components and asymmetric electrodes of the present invention.

[0041] The present invention also provides a lead-free ferroelectric ceramic material with a high degree of asymmetric large deformation, which is prepared by the lead-free ferroelectric ceramic material preparation method with a high degree of asymmetric large deformation. The lead-free ferroelectric ceramic material with a high degree of asymmetric large deformation has a composition of 0.733 (Bi 1 / 2 Na 1 / 2 )TiO3-0.267(Ca 1 / 3 Bi 2 / 9 Sr 1 / 3 )Cu3(Ti 1 / 2 Zr 1 / 2 )4O12 .

[0042] The lead-free ferroelectric ceramic material with highly asymmetric large deformation of the present invention is designed for the following purposes: 1 / 2 Na 1 / 2 )TiO3 has strong ferroelectric properties and large strain, but the remnant polarization of its ferroelectric hysteresis loop is large, resulting in a high negative strain in the strain curve and a low actual output drive strain. Figure 2 In order to reduce the residual polarization and negative strain while minimizing the maximum ferroelectric polarization and to generate the largest possible strain, a non-ferroelectric high polarity component (Ca 1 / 3 Bi 2 / 9 Sr 1 / 3 )Cu3(Ti 1 / 2 Zr 1 / 2 )4O 12 Through a large number of experiments and calculations, we found that the ratio of ferroelectric to non-ferroelectric is 0.733:0.267. The ceramic of this system is just at the critical component of the transformation from non-ergodic relaxation state to ergodic relaxation state. Its negative strain disappears and the output strain is the largest. Figure 3 Based on this large strain, we designed an asymmetric electrode. The electrodes on the two surfaces are composed of silver electrodes and gold electrodes respectively. The electrode radius ratio is 3:6.3. The center positions of the two surface electrodes are the same. Through the synergistic effect of the asymmetric electrode composition and size, it leads to non-uniform strain, resulting in a highly asymmetric deformation output. Figure 4 The present invention achieves the driving capability of outputting a piezoelectric bimorph in bulk ceramics, and these performances currently exceed those of lead-free ferroelectric ceramics in the prior art.

[0043] What is disclosed above is only one or more preferred embodiments of the present application, and cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiments and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. A method for preparing a lead-free ferroelectric ceramic material with highly asymmetric large deformation, characterized in that: include: According to 0.733 (Bi 1 / 2 Na 1 / 2 )TiO3-0.267(Ca 1 / 3 Bi 2 / 9 Sr 1 / 3 )Cu3(Ti 1 / 2 Zr 1 / 2 )4O 12 The analytically pure raw materials Bi2O3, Na2CO3, CaCO3, SrCO3, ZrO2, CuO and TiO2 are weighed respectively according to the chemical measurement, all the raw materials are mixed and ball-milled, the raw materials are dried after ball-milling, and the raw materials are kept warm and synthesized after drying to obtain powder; The synthesized powders are mixed and ball-milled, dried, cold isostatically pressed at 80 MPa, sintered into dense ceramics after heat preservation, and cooled to room temperature in air; Silver electrodes are screen-printed on one side of the sintered dense ceramic and gold electrodes are screen-printed on the other side. The center positions of the two surface electrodes are the same. After heat preservation, they become asymmetric electrodes of size, thereby obtaining a lead-free ferroelectric ceramic material with highly asymmetric large deformation.

2. A method for preparing a lead-free ferroelectric ceramic material with highly asymmetric large deformation according to claim 1, characterized in that: According to 0.733 (Bi 1 / 2 Na 1 / 2 )TiO3-0.267(Ca 1 / 3 Bi 2 / 9 Sr 1 / 3 )Cu3(Ti 1 / 2 Zr 1 / 2 )4O 12 The analytically pure raw materials Bi2O3, Na2CO3, CaCO3, SrCO3, ZrO2, CuO and TiO2 are weighed respectively according to the chemical measurement, all the raw materials are mixed and ball-milled, and the raw materials are dried after ball-milling. After drying, the raw materials are kept warm for synthesis. In the step of obtaining the powder, the ball-milling time is 24 hours, the insulation temperature is 910°C, and the insulation time is 3 hours.

3. The method for preparing a lead-free ferroelectric ceramic material with highly asymmetric large deformation according to claim 1, characterized in that: The synthesized powders are mixed and ball-milled and then dried, cold isostatically pressed at 80 MPa, and then sintered into dense ceramics after insulation, and cooled to room temperature in air, with a ball-milling time of 24 hours, an insulation temperature of 1080° C., and an insulation time of 1 hour.

4. The method for preparing a lead-free ferroelectric ceramic material with highly asymmetric large deformation according to claim 1, characterized in that: In the step of screen-printing a silver electrode on one side of the sintered dense ceramic and a gold electrode on the other side, with the centers of the two surface electrodes being the same, and forming asymmetric electrodes of size after heat preservation to obtain a lead-free ferroelectric ceramic material with highly asymmetric large deformation, the heat preservation temperature is 600°C and the heat preservation time is 30 minutes.

5. The method for preparing a lead-free ferroelectric ceramic material with highly asymmetric large deformation according to claim 1, characterized in that: The radius ratio of the silver electrode to the gold electrode is 3:6.

3.

6. A lead-free ferroelectric ceramic material with highly asymmetric large deformation, prepared by the method for preparing a lead-free ferroelectric ceramic material with highly asymmetric large deformation according to any one of claims 1 to 5, characterized in that: The composition of the lead-free ferroelectric ceramic material with highly asymmetric large deformation is 0.733 (Bi 1 / 2 Na 1 / 2 )TiO3-0.267(Ca 1 / 3 Bi 2 / 9 Sr 1 / 3 )Cu3(Ti 1 / 2 Zr 1 / 2 )4O 12 .